2013
DOI: 10.1080/00380768.2013.862157
|View full text |Cite
|
Sign up to set email alerts
|

Grazing exclusion alters soil microbial respiration, root respiration and the soil carbon balance in grasslands of the Loess Plateau, northern China

Abstract: Grassland ecosystems are a significant component of the global carbon cycle. To better understand how grazing affects the carbon cycle of grasslands, soil microbial respiration (Rm) and root respiration (Rr), which are the main soil respiration components, we investigated with a trenching method in grazed grasslands (GG) and fenced (FG) grasslands on the Loess Plateau, northern China in 2008. The annual carbon balance in the two grasslands were also assessed and compared. After exclusion of grazing for about 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 49 publications
2
19
0
2
Order By: Relevance
“…The mechanisms involved in SOC changes in response to grazing exclusion during grassland restoration are not clear. There are some indications in the literature that the SOC changes are most likely attributable to the following: Grazing exclusion boosts net primary production of the grassland due to reduced grazing pressure (Huang, Brümmer, & Huntsinger, ; Wang, Johnson, Rong, & Wang, ), leading to increased plant biomass accumulation on the soil surface (Li et al, ). The reduction in grazing pressure also leads to more belowground root biomass than aboveground biomass, and the increased root: Shoot ratio accelerates SOC accumulation (Liu, Liu, Wu, Wang, & Chen, ). With grazing exclusion, the cessation of animal trampling enhances soil aggregation that fosters physical protection of SOC, and the increased input of organic matter acts as binding agents for aggregation.…”
Section: Grazing Exclusion and Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms involved in SOC changes in response to grazing exclusion during grassland restoration are not clear. There are some indications in the literature that the SOC changes are most likely attributable to the following: Grazing exclusion boosts net primary production of the grassland due to reduced grazing pressure (Huang, Brümmer, & Huntsinger, ; Wang, Johnson, Rong, & Wang, ), leading to increased plant biomass accumulation on the soil surface (Li et al, ). The reduction in grazing pressure also leads to more belowground root biomass than aboveground biomass, and the increased root: Shoot ratio accelerates SOC accumulation (Liu, Liu, Wu, Wang, & Chen, ). With grazing exclusion, the cessation of animal trampling enhances soil aggregation that fosters physical protection of SOC, and the increased input of organic matter acts as binding agents for aggregation.…”
Section: Grazing Exclusion and Soil Propertiesmentioning
confidence: 99%
“…This process favors plant biomass accumulation and thus more input of organic matter into the soil. The change in grassland SOC is a result of plant–soil–microbiome interactions. Grazing exclusion enhances the carbon accumulation in the soil but at the meantime, it increases soil microbial respiration that depletes soil carbon (Li et al, ). Ultimately, the magnitude of the effect of grazing exclusion on the quantity of SOC is a function of the amount of organic matter input and the turnover process. The magnitude of the SOC change with grazing exclusion is highly related to abiotic (soil temperature, soil water content, and soil nutrient content), biotic (plant community structure, litter input, and microbial activity), and climatic and geographical factors (T. Chen, Nan, et al, ; Wittmer, Auerswald, Bai, Schäufele, & Schnyder, ).…”
Section: Grazing Exclusion and Soil Propertiesmentioning
confidence: 99%
“…Globally, overgrazing by livestock is one of the most important human induced causes of arid and semiarid grasslands degradation, such as lower grass yields, carrying capacity, soil nutrient content (Gass and Binkley, 2011;Li et al, 2013;McSherry and Ritchie, 2013). The effect of overgrazing on the plant community and on soil resources are considered destructive because it reduces vegetation cover Wu et al, 2013;Wang et al, 2014) and compacts soil as a direct result of trampling (Shi et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Grazing exclusion by fencing was conducted as an effective restoration and management regime, for grazing exclusion restored soil structure, soil nutrients and returned grazing potential Gass and Binkley, 2011;Wu et al, 2013;Wang et al, 2014). Some research works have been conducted to study the effects of grazing exclusion on carbon sequestration (Qiu et al, 2013;Wang et al, 2014), soil microbial respiration and root respiration (Li et al, 2013), ecosystem respiration and net ecosystem exchange (Du et al, 2012). Owensby et al (2006) concluded that both grazing exclusion and grazing tallgrass prairie appeared to be carbon-storage neutral and grazing was not a viable option to increase carbon sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…Land use in the Loess Plateau has undergone great changes in the past five decades (Li et al, 2013). Some researches indicated that grassland establishment on previously cultivated cropland increased LF dry matter, and consequently increased the storages of SOC in LF (Liu et al, 2010).…”
mentioning
confidence: 99%